Hubungan Dukungan Sosial Teman Satu Tim Dengan Kepercayaan Diri Saat Bertanding Pada Atlet Futsal SMAN 2 Ponorogo - Dellvico Daffa Herdiansyach; Abdul Aziz Hakim (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Social support is an action given to someone, especially when they need it, especially when someone is connected to each other emotionally. Social support can include feelings of comfort, care, self-esteem, and all forms of appreciation given to someone by the group. Social support increases a person's self-confidence to be able to control their feelings and strengths. This research aims to determine whether there is a relationship between teammate social support and self-confidence. The sample consisted of 30 male students from the futsal extracurricular at SMAN 2 Ponorogo. The results of this research used a correlational descriptive method with data collected through closed questionnaires. Analysis results Based on the data that has been taken, it produces a Pearsson correlations value of 0.610 and a significance value of 0.000<0.05. With the results obtained, the variables of teammate social support and self-confidence have a strong relationship, the stronger the teammate's social support. the more an athlete's self-confidence increases. The research results were also strengthened by normality and linearity tests where the data distribution showed a normal relationship with a significance result of 0.200>0.05 and the data also showed linearity with a deviation from linearity value of 0.352>0.05. Based on the results of data analysis, it can be concluded that there is a relationship between social support from teammates and self-confidence in futsal athletes at SMAN 2 Ponorogo. Providing maximum social support to athletes can increase the athlete's sense of responsibility and self-confidence. Thus, social support has a very important role for athletes to provide maximum abilities in competitions. Based on these results, this research hypothesis is accepted.